Optimizing CDK4/6 inhibitors in advanced HR+/HER2- breast cancer: A personalized approach. (December 2022) - Fontanella, Caterina; Giorgi, Carlo Alberto; Russo, Stefania; Angelini, Silvia; Nicolardi, Linda; Giarratano, Tommaso; Frezzini, Simona; Pestrin, Marta; Palleschi, Dario; Bolzonello, Silvia; Parolin, Veronica; Haspinger, Eva R.; et al.
Abstract: Cyclin-dependent kinase 4/6 inhibitors (CDK4/6i) combined with endocrine therapy (ET) are now a backbone of treatment for hormone receptor-positive/human epidermal growth factor receptor 2 (HER2)-negative advanced breast cancer. CDK4/6i plus ET is more effective than ET alone in this setting; however, the risk of grade 3–4 adverse events also increases. Approved agents in this class have similar efficacies, but important differences due to their structural and pharmacological properties. We review biomarkers and discuss determinants to inform a rational approach to therapy choice when selecting the most appropriate ET and CDK4/6i partners. We also identify subgroups that may benefit from specific ET-CDK4/6i combinations and discuss strategies to overcome resistance. This personalized approach aims to minimize treatment-related toxicities that may affect patient QoL and compliance, and ultimately therapy efficacy. Graphical Abstract: ga1 Highlights: The combination of CDK4/6i + ET is more effective than ET alone for the treatment of advanced BC; however, the risk of 3–4 grade AEs increase. The efficacy of ET and CDK4/6i therapy is challenged by occurrence of resistance. Although no randomized head-to-head comparative trials have been conducted, palbociclib, ribociclib and abemaciclib seem to provide comparable benefit in first-line and second-line as well. Few predictive and prognostic biomarkers have been clinically validated; no biomarker of CDK4/6i resistance is currently available.